Accurate measurement and quantitative analysis of 3D shape characteristics of irregular gangue blocks. (1st August 2022) - Li, Junmeng; Huang, Yanli; Ouyang, Shenyang; Zhao, Gang; Guo, Yachao; Gao, Huadong; Wu, Laiwei
Highlights: The digital 3D model of the real shape of irregular gangue particles was obtained. The shape measurement program of the random gangue particles was developed. The sensitivity ( S ) of shape index to the real shape of gangue particles is different. The frequency distribution histograms of the shape index are all skewed distribution. The larger the volume of gangue block, the more regular the gangue particles shape. Abstract: The mechanical properties of the crushed gangue, such as compression deformation characteristics and seepage characteristics, are closely related to the 3D shape characteristics of gangue blocks. In this study, the proportional 3D digitized models of gangue blocks were established, and the information reading program of the digitized 3D model was independently developed. Finally, a quantitative analysis was carried out to explore the elongation, flakiness, sphericity and other 3D shape characteristics of gangue blocks. Through a series of tests and analysis, the conclusions are summarized as follows: (1) the sensitivity ( S ) of different shape indexes of gangue blocks in characterizing the real shape of gangue block is different, and S elongation  >  S flakiness  >  S sphericity ; the average elongation, flakiness and sphericity of a random gangue block is about 1.5, 0.7 and 0.8; (2) the frequency distribution histogram of the elongation, flakiness and sphericity of gangue blocks in groups present a skewed distribution, among which the elongation has the positive-skewed distribution, and flakiness and sphericity have the negative-skewed distribution; (3) the larger volume of the gangue block indicates the smaller fluctuation range of elongation, flakiness and sphericity, the smaller difference between blocks, and the more regular shape of the gangue block. The research results of this paper can provide basic data support for studying the influence of gangue block shape on its engineering mechanical properties. Furthermore, based on the research conclusions of this paper, the bearing and compression performance of broken gangue materials can be designed by controlling the shape of gangue blocks in engineering application, so as to achieve the expected bearing capacity and ensure the filling effect of engineering site.